2009
DOI: 10.1177/152692480901900415
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Nursing Staff toward Organ Donation in a Spanish Hospital with a Solid-Organ Transplant Program

Abstract: Attitudes toward organ donation among nurses are similar to attitudes of the general public in Spain. Given the influence of nurses on the general public, promotional campaigns directed at nurses are a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…This observation that many healthcare professionals do not always exhibit prodonation behaviours has been reported previously. [17][18][19][20][21][22][23][24] A considerable proportion of participants indicated that they associated registering as an organ donor with issues of mortality and this may help explain the relatively low level of donation. It has been suggested that the exhibition of unusually high levels of fear or anxiety about death can prevent people from associating themselves with a behaviour that requires them to consider their own mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This observation that many healthcare professionals do not always exhibit prodonation behaviours has been reported previously. [17][18][19][20][21][22][23][24] A considerable proportion of participants indicated that they associated registering as an organ donor with issues of mortality and this may help explain the relatively low level of donation. It has been suggested that the exhibition of unusually high levels of fear or anxiety about death can prevent people from associating themselves with a behaviour that requires them to consider their own mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals are the basic link between society and the healthcare system, and their knowledge and attitudes are therefore key factors in increasing awareness of donation not only in society as a whole, but also within the health system itself. (Zambudío et al , ; Pont et al , ). Researchers have found that some healthcare staff (HS) are unfamiliar with the process of donation and the diagnosis of brain death (Marck et al , , b; Siminoff et al , ), while a negative attitude on their part can have serious repercussions on public opinion, generating a lack of confidence in the donation process (Traino et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant gap in knowledge exists with regards to the opinions and attitudes of nurses, who are the allied health professionals most frequently involved in donor tissue collection [11]. It is notable that whilst nurses play a leading role in the donation and transplantation system [11], the emergence of evidence suggests that this group of health professionals commonly exhibit concerns about their lack of knowledge of organ donation [12][18]. Due to the existence of these gaps in knowledge [12][18] and the low levels of provisions afforded to health professionals to undertake appropriate training [19]–[20]; health professionals' opinions and practices will therefore more likely be based on a personal locus of control.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that whilst nurses play a leading role in the donation and transplantation system [11], the emergence of evidence suggests that this group of health professionals commonly exhibit concerns about their lack of knowledge of organ donation [12][18]. Due to the existence of these gaps in knowledge [12][18] and the low levels of provisions afforded to health professionals to undertake appropriate training [19]–[20]; health professionals' opinions and practices will therefore more likely be based on a personal locus of control. This perspective may create conflict for the health professional and affect their ability to engage in pro-social behaviours [21][28].…”
Section: Introductionmentioning
confidence: 99%